Variação da Lateral Palatal na Comunidade de Jacaraú (Paraíba) - Freire, Josenildo Barbosa (2011)
This dissertation aims at analyzing the lateral palatal segment in the paraibano dialect of Brazilian Portuguese and its variants (palatal [λ], alveolar [l], glide [j] and deletion [Ø]), under the theoretical-methodological model of the Variation Theory proposed by William Labov (1966, 1972), describing the structural and social constraints underneath. The synchronic corpus was produced from 36 individuals of the speech community of Jacaraú (Paraíba) and is socially stratified according to sex, age and years of schooling. Linguistic and extra-linguistic variables which were likely to influence the variation were taken into consideration. This study also intends to analyze the behavior of that variation in texts from the 18th century, and to present the arboreal representations of the lateral segment according to the Geometry of Phonological Features (CLEMENTS & HUME, 1995). The software Goldvarb X (SANKOFF, TAGLIAMONTE & SMITH, 2005), a variable rule program used as a tool for the quantitative data, selected sex (feminine), age (15 to 25), years of schooling (1 to 8), following phonological context (labial vowel), preceding phonological context (coronal vowel) and number of syllables (trisyllabic) as the most relevant variables in the variation of the lateral palatal segment in the speech community of Jacaraú (Paraíba).